Expression Level of the DREB2-Type Gene, Identified with Amplifluor SNP Markers, Correlates with Performance, and Tolerance to Dehydration in Bread Wheat Cultivars from Northern Kazakhstan - Shavrukov, Yuri; Zhumalin, Aibek; Serikbay, Dauren; Botayeva, Makpal; Otemisova, Ainur; Absattarova, Aiman; Sereda, Grigoriy; Sereda, Sergey; Shvidchenko, Vladimir; Turbekova, Arysgul; Jatayev, Satyvaldy; Lopato, Sergiy; et al. (Frontiers in Plant Science, 2016)
A panel of 89 local commercial cultivars of bread wheat was tested in field trials in the dry conditions of Northern Kazakhstan. Two distinct groups of cultivars (six cultivars in each group), which had the highest and the lowest grain yield under drought were selected for further experiments. A dehydration test conducted on detached leaves indicated a strong association between rates of water loss in plants from the first group with highest grain yield production in the dry environment relative to the second group. Modern high-throughput Amplifluor SNP technology was applied to study allelic variations in a series of drought-responsive genes using 19 SNP markers. Genotyping of an SNP in the TaDREB5 (DREB2-type) gene using the Amplifluor SNP marker KATU48 revealed clear allele distribution across the entire panel of wheat accessions, and distinguished between the two groups of cultivars with high and low yield under drought. Significant differences in expression levels of TaDREB5 were revealed by qRT-PCR. Most wheat plants from the first group of cultivars with high grain yield showed strong up-regulation of TaDREB5 transcript in dehydrated leaves. In contrast, expression of TaDREB5 in plants from the second group of cultivars with low grain yield was significantly down-regulated. It was found that SNPs did not alter the amino acid sequence of TaDREB5 protein. Thus, a possible explanation is that alternative splicing and up-stream regulation of TaDREB5 may be affected by SNP, but these hypotheses require additional analysis (and will be the focus of future studies).